Javaphilia American Love Affairs with Javanese Music and Dance - Spiller, Henry (Music and Performing Arts of Asia and the Pacific, 2015)
Fragrant tropical flowers, opulent batik fabrics, magnificent bronze gamelan orchestras, and, of course, aromatic coffee. Such are the exotic images of Java, Indonesia's most densely populated island, that have hovered at the periphery of North American imaginations for generations. Through close readings of the careers of four "javaphiles"—individuals who embraced Javanese performing arts in their own quests for a sense of belonging—Javaphilia: American Love Affairs with Javanese Music and Dance explores a century of American representations of Javanese performing arts by North Americans.